Representações do boêmio na Vida noturna de Aldir Blanc - Rodrigues, Wellington Girardi (2023)
More so than a genre of marketing characteristics and with the intention of being a “soundtrack” of daily affairs, songs can be understood as a way of representing the misfortunes of society and its characters. The research is supported by this idea, in the studies of Social Representations (SR) by Serge Moscovici (1978; 2007), and in studies on Brazilian popular song, and aims to understand how Aldir Blanc represented the bohemian in his album “Vida Noturna” (2005). Seigel (1992) and Carvalho (1989) argue that the bohemian is a social being, born with modernity, and found on the threshold between the cultural and the countercultural, as if on a tightrope, shaping the concept of “artist”. The thesis supports the hypothesis that the composer builds positive representations of the bohemian way of life by locating the album's songs in a nocturnal environment, normally portrayed as reprehensible by the work society. The course of the analysis shows how the composer unites poetry with music and represents the aspects that shape the bohemian, revealing their subtleties, their joys, their sadness and their social role.